Optimization of Employee Certification System UI Using User-Centered Design Model - Shelya Putri Nurhaliza Abdillah; Dian Permata Sari (Dinasti Publisher, 2025)
A digital-based employee certification system plays a crucial role in ensuring compliance with industry standards while enhancing employee engagement and productivity. However, a less intuitive interface design remains a challenge in its implementation. This study aims to evaluate the usability of an employee certification website using the User-Centered Design (UCD) approach and the System Usability Scale (SUS) to enhance user experience and information accessibility. The research method involved system testing by 30 employee respondents as primary users, with evaluations based on the SUS. The analysis results indicate that the system achieved an average SUS score of 84.8, classified as